Pengelolaan zakat berbasis kelembagaan dan dampaknya terhadap pemberdayaan ekonomi mustahik: Studi pada badan amil zakat nasional (BAZNAS) kota Pasuruan - Firmansyah, Muzakki Ahmad (Maliki Interdisciplinary Journal, 2026)
Zakat is an Islamic economic instrument that plays a role in income redistribution, improving social welfare, and empowering the economy of mustahik (zakat beneficiaries). However, the optimization of zakat management still faces several challenges, including low public participation in distributing zakat through official institutions and the underutilization of zakat for sustainable economic empowerment programs. These conditions indicate the importance of institutional-based zakat management to ensure that the collection, distribution, and utilization of zakat are carried out in a more systematic, transparent, and accountable manner. This study aims to analyze institutional-based zakat management at BAZNAS Pasuruan City and its impact on the economic empowerment of mustahik. This study employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation at BAZNAS Pasuruan City and analyzed descriptively based on field findings and relevant supporting literature. The results indicate that zakat management at BAZNAS Pasuruan City has been implemented through a structured institutional system supported by organizational role distribution, SIMBA implementation, and management principles emphasizing sharia compliance, regulations, and accountability. Zakat management is not only focused on collection and distribution but is also directed toward productive programs in the form of business capital assistance, mentoring, and marketing support, which contribute to the economic empowerment of mustahik and gradually improve their economic independence. Therefore, institutional-based zakat management plays an important role in optimizing zakat as an instrument for community economic empowerment.